Hölderlin e a poética do paradoxo (Revista Eletrônica Estudos Hegelianos, 2021)
This article seeks to clarify and expose the principle of Hölderlin’s “poetic logic”, as it appears in the “poetological” texts, mainly in the Observations on Oedipus and Antigone. As we try to show here, Hölderlin’s “poetic logic” does not follow the principles of formal logic, but it comes close to dialectical logic, although it cannot be reduced to Hegelian dialectics. The logic here is not aimed at standardizing the rules of the use of thought, but at poetic practice, whose nature, in Hölderlin’s sense, consists in the paradoxical apprehension of existence as such. Although it can be more clearly observed in the tragic genre, this paradoxical logic of poetry also permeates Hölderlin’s so-called late hymns, such as Patmos and Bread and wine, in which tragic oppositions are coated in the elegiac form.